IMF Survey : Volume 28, Issue 11. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1999)
Following are edited excerpts from an address given by IMF Managing Director Michel Camdessus at the twenty-fourth annual conference of the International Organization of Securities Commissions (IOSCO) in Lisbon, Portugal, on May 25. The full text is available on the IMF's website (http://www.imf.org).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet